2018
DOI: 10.3390/rs10010149
|View full text |Cite
|
Sign up to set email alerts
|

A Satellite-Based Model for Simulating Ecosystem Respiration in the Tibetan and Inner Mongolian Grasslands

Abstract: Abstract:It is important to accurately evaluate ecosystem respiration (RE) in the alpine grasslands of the Tibetan Plateau and the temperate grasslands of the Inner Mongolian Plateau, as it serves as a sensitivity indicator of regional and global carbon cycles. Here, we combined flux measurements taken between 2003 and 2013 from 16 grassland sites across northern China and the corresponding MODIS land surface temperature (LST), enhanced vegetation index (EVI), and land surface water index (LSWI) to build a sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…Globally, temperature and precipitation are known to be important regulators of Rs, although their influence may vary between ecosystem types . Additionally, previous studies have demonstrated the relationships between EVI, vegetation productivity, soil carbon content, and rates of Rs (Chen et al, 2014;Ge et al, 2018).…”
Section: General Predictor Effects In Qrf Modelmentioning
confidence: 91%
“…Globally, temperature and precipitation are known to be important regulators of Rs, although their influence may vary between ecosystem types . Additionally, previous studies have demonstrated the relationships between EVI, vegetation productivity, soil carbon content, and rates of Rs (Chen et al, 2014;Ge et al, 2018).…”
Section: General Predictor Effects In Qrf Modelmentioning
confidence: 91%
“…Grasslands and their huge variety of types are almost never included as a separate category in remote sensing models of carbon flux, and as such are certain to be over or under-estimated. Ge et al (2018) proposed similar models to evaluate grassland R e at a regional scale by integrating flux measurements and the corresponding MODIS products. But this study simplified the grasslands in northern China by alpine grasslands and temperate grasslands.…”
Section: Discussionmentioning
confidence: 99%
“…But the model cannot be transferred well to specific ecosystems, and may particularly be inaccurate in hydrologically sensitive areas owing to lack of water index affecting R e . Nevertheless, previous studies have implied the significant correlations between grassland respiration and vegetation growth status (Huang et al, 2013), as well as the environmental variables such as LST (Wohlfahrt et al, 2008;Ai et al, 2018;Ge et al, 2018) from the time-series satellite data.…”
mentioning
confidence: 99%
“…Grasslands and their huge variety of types are almost never included as a separate category in remote sensing models of carbon flux, and as such are certain to be over or under-estimated. Ge et al [30] proposed similar models to evaluate grassland R e at a regional scale by integrating flux measurements and the corresponding MODIS products. But this study simplified the grasslands in northern China by alpine grasslands and temperate grasslands.…”
Section: Table 2 Pearson Correlation Analysis Between 8-day R E and Tmentioning
confidence: 99%
“…But the model cannot be transferred well to specific ecosystems, and may particularly be inaccurate in hydrologically sensitive areas owing to lack of water index affecting R e . Nevertheless, previous studies have implied the significant correlations between grassland respiration and vegetation growth status [25], as well as the environmental variables such as LST [15,17,30] from the time-series satellite data.…”
mentioning
confidence: 99%